A mindfulness based digital production youth center in Batangas City - Magsino, Meirah Kristel
While social media brings about different advances and improvements in our everyday lives, excessive and passive use creates high levels of sedentary behavior further increasing the risk for developing depressive and anxiety disorders (Strickland, 2014). This posed a threat to the youth who are identified as the top consumers of this media, as its passive overuse may lead to perceived isolation, lack of connection, low confidence and self-esteem, sleep deprivation, and other mild mental health issues among the youth. Batangas City was chosen as the local because the population distribution showed that its population is dominated by the youth, specifically the age groups 15-19 years old and 20-24 years old. It also serves as a cultural and educational hub not only of the province but also by its neighboring cities and provinces. Adapting to the needs of the youth today, the study aimed to design a structure which introduces new activities and behaviors, replacing the target users' passive and excessive social media use while utilizing psychiatric and cognitive concepts for the promotion of preventive psychiatry.